ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI PADA SISWA KELAS XI SMA SEBAGAI DASAR RANCANGAN MEDIA EDPUZZLE DAN BAMBOOZLE DI SMAN 11 BULUKUMBA - Rani Awalia Putri; Meilina Julhijah; Andi Ika Prasasti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze students' needs for technology-based learning media at SMAN 11 Bulukumba as a foundation for developing interactive tools such as Edpuzzle and Baamboozle. This research employed a descriptive qualitative approach with data collection techniques including classroom observation, in-depth interviews, and questionnaires distributed to Grade XI students. The results indicate that the majority of students are not yet accustomed to using interactive media; however, they demonstrate strong enthusiasm for technology-integrated learning. Students expressed a preference for learning media that support interactive features, independent access, and the presentation of content that is engaging, contextual, and relevant to their needs. These findings highlight the importance of developing technology-based learning media that are adaptive, participatory, and aligned with students’ characteristics and learning preferences.